TRANSFER INFORMASI INTRAINDUSTRI PADA PENGUMUMAN KENAIKAN DIVIDEN - Ratna Hidria DPS (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2017)
The aim of this research is to test intra-industry transfer in the announcement of dividend increase in Indonesia Stock Exchange. This research is to prove the behaviour of competitor companies (nonreporter) in the same industry with company which makes the announcement of dividend increase (reporter) to the companies. The latest samples are 381 companies. The result of this test is showing that announcement of devidend increase has a significant effect to the judgement of companies which are not make the announcement. This announcement is make a competitive effect. This effect shows that the good news from the reporter company will be bad news for the other companies in the same industry. The statistic menthod which is used to test the hypothesis is t test. This research is also used to test the reaction from the nonreporter companies which already or not yet announce their devidend. The result of this test shows that there are no difference reaction from the nonreporter companies, which already or not yet announce their dividend. It means that investors more interest to get some profit from capital gain than dividend.Keyword: transfer of information, intraindustry, dividend